2016
DOI: 10.1007/s00520-016-3375-z
|View full text |Cite
|
Sign up to set email alerts
|

Treating an oft-unrecognized and troublesome entity: using gastric electrical stimulation to reduce symptoms of malignancy-associated gastroparesis

Abstract: A small sample of patients with MAG and receiving temporary GES experienced symptom improvement, with less change on gastric emptying time or gastric electrical amplitude or frequency. GES may provide a potential therapeutic option for symptomatic management of MAG and evaluation of these MAG patients after permanent GES placement is ongoing. Prospective studies of MAG using temporary and permanent GES may be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…If symptoms do not respond to dietary changes, glucose control, narcotic elimination, prokinetics, and antiemetics, then patients are considered as refractory cases. For refractory cases, a GES device may be considered [10, 11]. Abell et al [12] demonstrated a significant postoperative increase in the physical and mental component scores, and a few studies [13, 14] also noted a significant increase in quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…If symptoms do not respond to dietary changes, glucose control, narcotic elimination, prokinetics, and antiemetics, then patients are considered as refractory cases. For refractory cases, a GES device may be considered [10, 11]. Abell et al [12] demonstrated a significant postoperative increase in the physical and mental component scores, and a few studies [13, 14] also noted a significant increase in quality of life.…”
Section: Discussionmentioning
confidence: 99%